Integrated Analysis of Long Non-Coding RNAs and mRNAs Reveals Key Trans-Target Genes Associated with Heat Stress Response in Rhododendron delavayi - Changming Liu; Yang Liu; Xinyue Zhang; Lujie An; Zhiguo Tian (Life)
Long non-coding RNAs (lncRNAs) have been defined as non-coding transcripts exceeding 200 nucleotides, which play essential roles during transcriptional and post-transcriptional regulation in multiple biological processes. Understanding R. delavayi lncRNAs is of great significance as it is profoundly influenced by heat stress. In this research, a total of 1145 differentially expressed lncRNAs (DE-lncRNAs) and 9447 differentially expressed genes (DEGs) (log2|FC| > 1, p < 0.05) were characterized between heat-stress-treated groups and control groups. Further analysis showed that 229 DE-lncRNAs (144 upregulated and 85 downregulated) were commonly distributed in two comparisons (CK_vs._H3 and CK_vs._H6). We further investigated the cis- and trans-acting genes of the upregulated DE-lncRNAs, and found that 142 upregulated DE-lncRNAs corresponded to 1565 cis-acting DEGs, and 143 upregulated DE-lncRNAs corresponded to 3417 trans-acting DEGs. KEGG enrichment analysis of these target genes revealed that cis- and trans-acting DEGs of upregulated DE-lncRNA were primarily enriched in five and twelve KEGG pathways, respectively. Co-expression network analysis of upregulated DE-lncRNAs and DEGs enriched in the common KEGG pathways revealed 57 co-expression relationships between 28 DE-lncRNAs and 43 cis-acting DEGs and 554 co-expression relationships between 26 DE-lncRNAs and 90 trans-acting DEGs. Six DE-lncRNAs and six of their target DEGs were used as candidate genes to verify the RNA-seq data using qRT-PCR. Further analysis revealed three target genes (TrxG, PEPC, and CCR) out of six candidate DEGs that were selected as candidate genes for subsequent research. This study examined the relationship between DE-lncRNAs and DEGs and further screened out candidate DE-lncRNAs that can potentially provide an important theoretical basis and experimental data for the genetic improvement of heat tolerance in R. delavayi.